P72 Diabetes mellitus in patients with autoimmune hepatitis (AIH): an independent adverse prognostic factor. (19th June 2022) - Flatley, Sarah; Dixon, Selena; Hoeroldt, Barbara; Harrison, Laura; Wadland, Elaine; Gleeson, Dermot
Abstract : Introduction: Diabetes is present in 5-10% of patients at diagnosis of AIH and develops later in a further 10-20%, usually associated with steroid therapy. The prognostic implications of diabetes in patients with AIH are unclear. We aimed to assess the association of diabetes with mortality in patients with AIH. Methods: Retrospective/prospective single-centre audit of patients with AIH (1999 IAIHG Criteria) presenting 1971-2021 and followed to death, liver transplant, loss to follow up, or to 31/12/2021. Diabetes was defined by WHO criteria or by starting antidiabetic drug treatment. Results: Of 519 patients (81% women, 92% Caucasian, median age 56 years, median follow up 9 years), 139 (27%) had cirrhosis and 95 (20%) had decompensation at diagnosis. 491 (95%) received steroids. Diabetes was present in 44 patients (9%) at AIH diagnosis and developed later in a further 65 (15%). Diabetes was Type 2 in 86%. 187 patients died (46 liver-related, 116 non-liver, 10 cause unknown) and 15 had a transplant. Death/transplantation rates after 10 and 20 years respectively were 20±2% and 51±3% (all-cause), and 8±1% and 21±3% (liver-related). We confirmed associations of death/transplantation rate with older age, cirrhosis and decompensation at diagnosis, and (liver only) not receiving steroids ( table 1 ). Diabetes (onset anytime) and diabetes (after AIH diagnosis) also showed associations with all-cause death/transplantation, on uni- and multi-variate analysis (incorporating other baseline prognostic variables). Diabetes (anytime) was also associated with liver-related death/transplantation. Conclusions: We report a novel association between diabetes and death/transplantation rate in AIH, that is independent of baseline prognostic variables.